Factors Affecting the Implementation of Green Banking Technology: Evidence from Digital Banking in Indonesia - Rahman, Faisal Fajri; Kuswendang, Wiwi; Komara, Acep; Muna, Arinal (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This study aims to investigate the factors that influence the adoption of digital banking, with the ultimate goal of increasing the acceptance of green banking technology. Design/methodology/approach: This study employs a mixed-methods approach, involving a survey of 466 digital banking users analyzed using SmartPLS 4.0. This data is strengthened through in-depth interviews with 30 respondents regarding the intention to use digital banking. Findings: The study's findings revealed that Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) have a positive influence on the intention to use green banking technology, mediated by User Satisfaction (US). Then, Perceived Value (PV) has a positive influence on the Intention to Use Green Banking Technology, and the role of Trust has the most significant positive influence. Research limitations/implications: This study has limited generalizability to its population sample due to the random data collection and lack of focus on specific user groups. Practical implications: This study demonstrates that the adoption of digital banking significantly reduces carbon emissions contributing to global warming by minimizing paper use and waste. Originality/value: This research can serve as a basis for developing more effective green banking policies, thereby encouraging sustainable economic growth in developing countries. Paper type: Research paper